Analisis Potensi Wisata Pantai - Herliana Bainpen; Melki I. Puling Tang; Ade Melisa Koilhing; Aderika Peni; Agustina Penikay; Erna Pulingtang; Herlina Batang (Jurnal Mahasiswa Kreatif, 2023)
The purpose of this study is to determine the tourism potential of Mali's beaches. Tourism potential is everything that is owned by a tourist spot that is an attraction for anyone who visits the place. Alor Regency is an area that has many destinations. One of them is beach tourism, which is beach tourism in Mali and has tourism potential that attracts the attention of tourists. Based on the results obtained from observations, interviews and researchers' observations about beach tourism in Mali, beach tourism in Mali is tourism with very good opportunities, namely good natural opportunities and will become a tourist destination with very beautiful nature. beauty . eye candy and the facilities there are very good which can be enjoyed during a beach tour in Mali. Apart from the natural beauty and excellent facilities, tourists can observe dugongs in the Pantar Straits Reserve (SAP), Kabola Subdivision which is about 20 minutes from the coast of Mali.